Viral Hepatitis B in Personnel of Betong Hospital - Ratanachu-ake, S. (Journal of Health Science of Thailand, 1993)
The prevalence of serologic markers of hepatitis B virus (HBV) infection was retrospectively studied in 237 Belong Hospital in a period from August to September 1990. The markers in this study were HBsAg and anti-HBs. An average prevalence of 2.1% for HBsAg and higher in male. Seroconvwesion was subsequently studied among 136 non-responders after receiving hepatitis B vaccine. The first group (108 personnel) received vaccine 1ml. (20ug) intramuscular and the second group (28 personnel) received vaccine 0.2 ml. intradermal. The vaccination schedule was two doses one month apart and booster dose at the sixth month. Antibody responses were measured after the booster dose. The result showed that seroconversion rate was 87.04% in each group respectively. There was no significant difference between the two groups. A rebooster (4th) dose was given to 19 personnel who had negative anti HBs at the twelveth month. The average seroconversion rate was found to increase from 86.03% to 91.18%.